2009
DOI: 10.1186/1471-2164-10-443
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of miRNAs expressed in the bovine ovary

Abstract: BackgroundMicroRNAs are the major class of gene-regulating molecules playing diverse roles through sequence complementarity to target mRNAs at post-transcriptional level. Tightly regulated expression and interaction of a multitude of genes for ovarian folliculogenesis could be regulated by these miRNAs. Identification of them is the first step towards understanding miRNA-guided gene regulation in different biological functions. Despite increasing efforts in miRNAs identification across various species and dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
104
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 84 publications
10
104
0
Order By: Relevance
“…An increase in the levels of all of these miRNAs in large follicles was accounted for increases in mural granulosa cells rather than in COC; this was not surprising as the latter contains a very small fraction of the total cells in the follicle, and therefore microarray analyses of whole follicle tissues might have missed changes in miRNA levels in the COC. Indeed, miRNAs differentially expressed in bovine COCs, cumulus cells or oocytes, in addition to changes in miRNA expression during oocyte maturation, have been reported (Hossain et al 2009, Miles et al 2012, and they did not include any of the miRNAs identified as enriched in large healthy follicles in this study. Nonetheless, our results suggest a potential involvement of bta-miR-144, bta-miR-202, bta-miR-451, bta-miR-652, and bta-miR-873 in the regulation of mural granulosa cell function during maturation of the dominant follicle, as their expression in all cases increased in healthy follicles once they reached a diameter of 12-14 mm.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…An increase in the levels of all of these miRNAs in large follicles was accounted for increases in mural granulosa cells rather than in COC; this was not surprising as the latter contains a very small fraction of the total cells in the follicle, and therefore microarray analyses of whole follicle tissues might have missed changes in miRNA levels in the COC. Indeed, miRNAs differentially expressed in bovine COCs, cumulus cells or oocytes, in addition to changes in miRNA expression during oocyte maturation, have been reported (Hossain et al 2009, Miles et al 2012, and they did not include any of the miRNAs identified as enriched in large healthy follicles in this study. Nonetheless, our results suggest a potential involvement of bta-miR-144, bta-miR-202, bta-miR-451, bta-miR-652, and bta-miR-873 in the regulation of mural granulosa cell function during maturation of the dominant follicle, as their expression in all cases increased in healthy follicles once they reached a diameter of 12-14 mm.…”
Section: Discussionmentioning
confidence: 86%
“…QPCR analyses confirmed that at least three of these miRNAs were also upregulated significantly in some or all of the large healthy follicle categories relative to large atretic follicles, thus identifying this set of miRNAs as very strong candidates with a role in the development of bovine dominant follicles. mir-144, mir-202, mir-451, and mir-652 were reported earlier to be expressed in the ovary (Hossain et al 2009, McBride et al 2012, Kitahara et al 2013, Schauer et al 2013, although their expression patterns within follicular tissues were not studied in detail. In this study, bta-miR-202 was restricted to the bovine gonad; moreover, its expression within the follicle was highest in granulosa cells while levels in ovarian stroma were negligible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…F X DONADEU and others 325 ), equine follicular fluid (da Silveira et al 2012) and bovine corpora lutea have been identified using mouse-or human-based microarray or highthroughput qPCR. Some studies reported differences in miRNA expression between different ovarian or follicular compartments, including expression of miR-503, miR-224 and miR-383 predominantly in mouse granulosa cells and oocytes of mice (Lei et al 2010, Yao et al 2010a, Yin et al 2012, as well as differential expression of several dozen miRNAs in bovine ovarian cortex, cumulus cells and corpus luteum (CL; Hossain et al 2009). Further, a correlation was reported between follicular fluid and granulosa cell levels of several miRNAs in horses (da Silveira et al 2012).…”
Section: Identification and Profiling Of Mirnas In Ovarian Tissuesmentioning
confidence: 99%
“…Small RNA populations have been identified by cloningbased or next-generation sequencing of normal ovarian tissues from human (Landgraf et al 2007), mice (Ro et al 2007, Mishima et al 2008, Ahn et al 2010, pigs , cattle (Hossain et al 2009, Tripurani et al 2010, Huang et al 2011, Miles et al 2012 and sheep (McBride et al 2012). Most of those studies involved analyses on whole ovaries rather than on specific ovarian tissue components, an approach that, although very useful for comprehensive identification of miRNA sequences, provides very limited insight into their functional relevance.…”
Section: Identification and Profiling Of Mirnas In Ovarian Tissuesmentioning
confidence: 99%